GIS Enhanced Disaster Management Coupled with Supporting Technologies in Intelligent Urban Environments - Sabila Rizqina Majid; Muhayat Muhayat; Husna Norgina (International Journal of Science and Environment (IJSE), 2026)
Efforts to understand the role of Geographic Information Systems (GIS) in the context of disasters are no longer enough to only look at their function as a mapping tool. This research departs from the problem of data integration that tends to be fragmented, and then tries to see how GIS works when dealing with data sources that are not always in line. The approach used was an Integrative Literature Review of 25 Scopus indexed articles, which were selected through several stages of screening, although not all studies offered the same depth. The analysis process is carried out through data extraction and thematic readings to capture emerging patterns, including parts that have not been discussed much. The results show that GIS tends to act as a meeting point for various types of data, ranging from satellite imagery to information based on public participation that is not always stable. In practice, technologies such as the Internet of Things, digital twins, Unmanned Aerial Vehicles, and WebGIS expand the way systems respond to situations, especially through real-time data and simulations that are predictive in nature. However, not all integrations go smoothly. Limited Interoperability, variations in data quality, and infirm governance are still quite noticeable obstacles. At this point, the potential of the system is obvious, but it is not yet fully ripe for reliability without further adjustments.